Leadership requirements for Lean versus servant leadership in health care: a systematic review of the literature - Aij KH; Rapsaniotis S (Dove Medical Press, 2017)
Kjeld Harald Aij, Sofia Rapsaniotis VU University Medical Center, Division Acute Care and Surgery, Amsterdam, The Netherlands Abstract: As health care organizations face pressures to improve quality and efficiency while reducing costs, leaders are adopting management techniques and tools used in manufacturing and other industries, especially Lean. Successful Lean leaders appear to use a coaching leadership style that shares underlying principles with servant leadership. There is little information about specific similarities and differences between Lean and servant leaderships. We systematically reviewed the literature on Lean leadership, servant leadership, and health care and performed a comparative analysis of attributes using Russell and Stone’s leadership framework. We found significant overlap between the two leadership styles, although there were notable differences in origins, philosophy, characteristics and behaviors, and tools. We conclude that both Lean and servant leaderships are promising models that can contribute to the delivery of patient-centered, high-value care. Servant leadership may provide the means to engage and develop employees to become successful Lean leaders in health care organizations. Keywords: management, leadership attributes, efficiency, patient-centered, high-value care